Azogabazine; a photochromic antagonist of the GABAA receptor. Issue 28 (21st June 2016) - Huckvale, Rosemary; Mortensen, Martin; Pryde, David; Smart, Trevor G.; Baker, James R.
Abstract : The design and synthesis of Azogabazine is described, which is shown to act as a highly potent, photoswitchable antagonist of the GABAA receptor. Abstract : The design and synthesis of azogabazine is described, which represents a highly potent (IC50 = 23 nM) photoswitchable antagonist of the GABAA receptor. An azologization strategy is adopted, in which a benzyl phenyl ether in a high affinity gabazine analogue is replaced by an azobenzene, with resultant retention of antagonist potency. We show that cycling from blue to UV light, switching between trans and cis isomeric forms, leads to photochemically controlled antagonism of the GABA ion channel.